Anemia-free strategies and antenatal care services in stunting prevention - Mizawati, Afrina; Effendi, Nursyirwan; Sulastri, Delmi; Purna, Rozi Sastra (BKM Public Health and Community Medicine, 2024)
Purpose: The purpose of this study was to evaluate the effectiveness of interventions targeting anemia prevention and antenatal care (ANC) to reduce the risk of stunting in children. Methods: A comprehensive search will be conducted in electronic databases to investigate the impact of anemia prevention strategies on child stunting. Studies will be included if they assess interventions in women focusing on iron supplementation, nutrition counseling, or a combination of both and report child stunting as an outcome measure. Results: Anemia prevention is very effective in improving children's growth outcomes, thus contributing to knowledge and ways of treating anemia in the preconception and antenatal periods to reduce the prevalence of stunting. Conclusion: The importance of comprehensive interventions in improving the health and well-being of future generations. Implementing health policies integrating blood supplementation interventions, nutrition education, and quality antenatal care is highly recommended to create a healthier and more qualified generation.